Study on cortisol, cortisone and prednisolone presence in urine of Chianina cattle breed. Issue 5 (14th April 2016) - Chiesa, L.; Pavone, S.; Pasquale, E.; Pavlovic, R.; Panseri, S.; Valiani, A.; Arioli, F.; Manuali, E.
Summary: The Chianina, one of the oldest and most important cattle breeds of Italy, is now reared all over the world. The Chianina has been known and appreciated since ancient times because, from a nutritional point of view, its meat has no proper rivals. To date, studies have been performed to evaluate the genetic profile of the breed, but knowledge about the chemical profile is generally lacking. Due to the increased interest from farmers regarding breeding of the Chianina, this study proposes a preliminary evaluation of main endogenous urinary corticosteroids (cortisol and cortisone) and most commonly used synthetic one (dexamethasone). Moreover, after recent findings regarding the presence of endogenous prednisolone in the urine of more popular breeds, particular attention was given to analysis of the presence of prednisolone and prednisone, as well. For this aim, the urine samples of 12 young cows and 30 young bulls was collected at the farms and analysed using a fit‐for‐purpose LC‐MS/MS method. The preliminary results of this study show that prednisolone was found only in Chianina females (3 out of 12). Cortisol and cortisone were found at concentrations that showed a high inter‐individual variability, and that were higher in female urine compared to that of males.